EFFECTIVENESS OF BOOKLETS AS EDUCATIONAL MEDIA TOINCREASE HYPERTENSION KNOWLEDGE: LITERATURE REVIEW - Mahardika Primadani; Isne Susanti; Eka Oktavia (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Hypertension is one of the chronic diseases with high prevalence that requires continuous educational efforts. Booklets as simple printed media are considered effective in increasing patient knowledge about the prevention and management of hypertension. This study is a literature review study that aims to analyze the effectiveness of using booklets as educational media in increasing knowledge of hypertension. Articles were obtained from the PubMed, Scopus, Web of Science, and Google Scholar databases using the keywords: